1996
DOI: 10.1111/j.1432-1033.1996.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a 60‐kDa Protein from Chicken Liver Associated with the Internal Nuclear Matrix and Closely Related to Carboxylesterases

Abstract: A 60-kDa protein was purified from chicken liver internal nuclear matrix and its nuclear localization was confirmed by immunofluorescence analysis. Structural information acquired from sequence analysis of the intact protein and of fragments obtained from enzymatic and chemical cleavages strongly suggests that it belongs to the carboxylesterases family, even if with some very peculiar features. The N-terminal sequence of the 60-kDa protein is completely different from the other carboxylesterases, but is simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…S.A), polyclonal anti-actin antibody (Sigma), and anti-chicken nuclear carboxylesterase rabbit serum (19). The last protein has been previously shown to be one of the nuclear matrix proteins that are unbound to DNA (F. Altieri and A. Ferraro, unpublished results).…”
Section: Dna-protein Complexes Purificationmentioning
confidence: 96%
See 1 more Smart Citation
“…S.A), polyclonal anti-actin antibody (Sigma), and anti-chicken nuclear carboxylesterase rabbit serum (19). The last protein has been previously shown to be one of the nuclear matrix proteins that are unbound to DNA (F. Altieri and A. Ferraro, unpublished results).…”
Section: Dna-protein Complexes Purificationmentioning
confidence: 96%
“…Figure 3 shows the results obtained with three different antibodies against nuclear proteins, anti-carboxylesterase (19), anti-actin, antiERp57. The three proteins are present in the nuclear fraction but only the actin and ERp57 are cross-linked to DNA, confirming the validity of our procedure.…”
Section: Immunoprecipitationmentioning
confidence: 97%
“…Observations using electronic microscopy and biochemical studies of chromosomes and nuclei lacking histones supported the hypothesis that eukaryotic DNA was organized in loops associated with the chromosomal skeleton (scaffold) or the nuclear matrix (Cook and Brazell, 1976;Paulson and Laemmli, 1977). Additional analyses demonstrated that these loops, roughly ranging from 5 to 100 kb or more, were anchored in the nuclear matrix through specific sequences called Scaffold Attached Regions (SARs) or Matrix Attached Regions (MARs) (Altieri et al, 1996;Berrios et al, 1985;Phi-Van and Strätling, 1990). The nuclear matrix forms a fibrogranular structure, resulting from the extraction of a high saline concentration (2M NaCl) or the use of detergents such as LIS (3.5 lithium diiodosalicilate).…”
Section: Introductionmentioning
confidence: 91%
“…However, it also depends on cell type, as well as the isolation procedure of the nuclear matrix, the internal network and/or the remaining nucleolar fraction, which may be absent, while the external lamina is present in all the extractions (Neri et al, 1997). A large number of proteins with enzymatic functions such as oxidoredutases, transferases, hidrolases and glycoproteins are found associated with the nuclear matrix (Altieri et al, 1996;Ferraro et al, 1994;S'iakste and S'iakste, 1994), as well as enzymes such as DNA and RNA polymerases, and DNA metilases and ligases, which are involved in the synthesis processes (processing and repairing) (Berrios et al, 1985;Stein et al, 1991;Berezney, 1987a, Vemuri et al, 1993). The presence of a minimum group of constituent proteins from the nuclear matrix such as topoisomerases, histone H1 and lamina, in plant and animal cells, suggests a conserved structure (Bouliskas, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation